STUDI TENTANG PERAN MASYARAKAT ADAT TERHADAP KELESTARIAN HUTAN ADAT KENEGERIAN RUMBIO KECEMATAN KAMPAR KABUPATEN KAMPAR - Sandi, Ari; Hambali, Hambali; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the importance of the role of indigenous peoples in maintaining the sustainability of indigenous forest of kenegerian Rumbio Kampar district of Kampar regency. In relation to that the authors take the title of research, "Studies on the Role of Indigenous Peoples Against the sustainability of indigenous forest Kenegerian Rumbio Kampar district Kampar regency". The formulation of the problem in this research is How the Role of Indigenous Peoples in Preserving Adat Forest of Kenegerian Rumbio Kampar Kabupeten Kampar. The purpose of this study is to see how the role of indigenous peoples in preserving customary forests in Rumbio Village, Kampar District. Respondents in the research were 75 indigenous peoples kenegerian Rumbio with purposive sampling technique. Techniques of collecting data is done through observation, questionnaires, interviews, documentation and literature. The research method used is descriptive quantitative method. Quantitative descriptive data analysis method is done by data processing with data result presented by percentage calculation and given explanation. Based on the result of the research, it can be concluded that the percentage of respondents' recapitulation of questionnaire responses on the Study of the Role of Indigenous Peoples on the sustainability of indigenous forest Kenegerian Rumbio Kampar district Kampar Regency seen from the percentage of 75 respondents who answered "YA" as much as 84% while the answer "NO" as much as 16% based on that percentage can be seen most of the community role to preserve indigenous forest.Keywords: Community Role, Sustainability, Customary Forest